El envejecimiento y la muerte: un enfoque filosófico - Jiménez Alfaro, Marco (2015)
In this essay, the author reflects on the topic of aging and its focal relation to the idea of death. The author integrates historical and scientific information and then complements a philosophical assessment. This is the aim of this essays. In the first part, the different conceptions of aging that have prevailed over time are explained, emphasizing the paradigmatic cases antagonistic as Plato and Aristotle, who would later central to the present. In the second part, a brief discussion of the concepts of longevity and aging, which finally allows him to associate the theme of old age with the idea of death from the philosophical framework is done as a question.